EHealth readiness of dietitians. Issue 4 (23rd February 2018) - Maunder, K.; Walton, K.; Williams, P.; Ferguson, M.; Beck, E.
Abstract: Background: The present study aimed to determine the eHealth readiness and changes over time of dietitians in Australia. Methods: Two cross‐sectional analyses of Australian dietitians were conducted in 2013 and 2016, using a survey adapted from one conducted in 2011 by the US Academy of Nutrition and Dietetics. The survey encompassed 30 questions on eHealth readiness across five dimensions: access, standards, attitude, aptitude and advocacy . Descriptive statistics, independent t ‐tests, chi‐squared tests and Z ‐tests were computed to compare responses from the 2013 and 2016 surveys. Results: The survey completion rate represented 14.5% (747) of the Dietitians Association of Australia members in 2013 and 8% (417) in 2016. The survey responses in relation to access and standards suggest that dietitians are well positioned for eHealth. For attitude and aptitude, there is a moderate level of preparedness, with minor improvements over time. Although showing significant improvement ( P < 0.05), advocacy highlights the area requiring the most development because the majority of dietitians (61%) reported 'no role' in eHealth solutions. Conclusions: Dietitians are progressing in relation to access, attitudinal and aptitudinal readiness for eHealth, although they rate poorly with respect to advocacy readiness. It was concluded that dietitians are not yet ready, and also that valuable opportunities to achieve the benefits that eHealth can deliver will be missed, if dietitians do not take the lead in guiding the development, selection and implementation of nutrition‐related technologies. Strengthening the dimension of advocacy and ensuring collaboration across the profession, drawing on the varying expertise demonstrated across the practice areas and by the different generations, will be central to improving dietitian eHealth readiness.